2015
DOI: 10.1590/0370-44672014680018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth ring orientation of some wood species to obtain toughness

Abstract: Wood toughness is a mechanical property of interest in structural design where the load impact must be considered, finding a strong application in bridges, however, not an integral part of the mechanical properties commonly investigated in the characterization of this material. This study aimed to investigate with the aid of variance analysis, the influence of growth ring orientation to obtain toughness for Angelim Saia (Parkia pendula), Eucalyptus grandis, Pinus elliottii and Corymbia citriodora wood species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This testing followed the prescriptions of Brazilian ABNT NBR 7190:1997 [25] and American ASTM D-143-14:2014 [26] standards for the following properties: density (bulk and volumetric mass); perpendicular and parallel compressions, perpendicular and parallel tensiles, and static bending (in modulus of rupture and elasticity parameters); shear stress; cleavage (tangential); hardness (parallel and perpendicular); and toughness (tangential). Tangential orientation was selected due to strength in parallel direction to growth rings, and supported by an observation by Stolf et al [27] claiming that there is no significant difference between radial and tangential toughnesses for dicotyledonous trees.…”
Section: Methodsmentioning
confidence: 99%
“…This testing followed the prescriptions of Brazilian ABNT NBR 7190:1997 [25] and American ASTM D-143-14:2014 [26] standards for the following properties: density (bulk and volumetric mass); perpendicular and parallel compressions, perpendicular and parallel tensiles, and static bending (in modulus of rupture and elasticity parameters); shear stress; cleavage (tangential); hardness (parallel and perpendicular); and toughness (tangential). Tangential orientation was selected due to strength in parallel direction to growth rings, and supported by an observation by Stolf et al [27] claiming that there is no significant difference between radial and tangential toughnesses for dicotyledonous trees.…”
Section: Methodsmentioning
confidence: 99%
“…This is evidenced by fiber layers that enable the development of cracks not only towards the load direction in a test but also perpendicular thereto (i.e., mixed mode). Therefore, wood anatomical composition makes it a highly tough material resistant to crack propagation (Morel & Valentin, 2005, Stolf et al, 2015, Xianwu et al, 2017, Fank et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original paper by the latter authors was written in Portuguese and is not easily accessible, we must rely here on just this short communication by the former authors. However, Stolf et al , after carefully conducted impact tests on samples obtained from parkia ( Parkia pendula ), flooded gum ( Eucalyptus grandis ), slash pine ( Pinus elliottii ) and lemon‐scented gum ( Corymbia citriodora ), concluded that direction of impact had no statistically significant effect on the value of toughness. Three directions of impact were tested in this experiment: radial towards the axis of the trunk, radial outwards, and tangential.…”
Section: Introductionmentioning
confidence: 99%